Anthropometric characteristics of adherents and dropouts of strength training - Andrade, Alexandro (2016)
Objective: The aim of this study was to compare the anthropometric profile of adherents and dropouts of strength training with different gender, age and civil status. Methods: 54 practitioners of strength training participated in this study, with average age 30 years. Participants were characterized according to gender, age and civil status and the anthropometric indicators (body weight, height, waist-hip ratio, body mass index and body fat). Data was analized by descriptive and inferential statistics. Results: Adherents and dropouts do not differ significantly from anthropometric indicators. Dropouts with partner, have a higher body fat and fat mass compared to those without partner. Adherents and dropouts over 30 have a higher body fat and fat mass than 30 years. Conclusion: Adherents and dropouts do not differ significantly from anthropometric indicators.